Answer:
Explanation:
m1 = 24 kg
m2 = 63 kg
(a) Let the tension is T1 in upper rope and T2 in lower rope.
Use Newtons' second law on m2.
[tex]T_{2}-m_{2}g = m_{2}a[/tex]
[tex]T_{2}= 63(9.8 + 3.8)[/tex]
T2 = 856.8 N
Apply Newton's second law on m1
[tex]T_{1}-T_{2}-m_{1}g = m_{1}a[/tex]
[tex]T_{1}-856.8 = 24(9.8+3.8)[/tex]
T1 = 1183.2 N
(b)
Use Newtons' second law on m2.
[tex]T_{2}-m_{2}g =- m_{2}a[/tex]
[tex]T_{2}= 63(9.8 - 3.8)[/tex]
T2 = 378 N
Apply Newton's second law on m1
[tex]T_{1}-T_{2}-m_{1}g = -m_{1}a[/tex]
[tex]T_{1}-378 = 24(9.8-3.8)[/tex]
T1 = 522 N